The Impact of State-Local Government Relations on Local Government Performance in Ogun State - Mahmud Osho; AbdulRauf Ambali (UNIDA Gontor, 2025)
This study examines the impact of state-local government relations on the performance of local governments in Ogun States, Nigeria, with an emphasis on how such relationship affects local government performances. Local governments are critical in driving economic development and delivering essential services to improve citizens' well-being. However, their performance is often constrained by imbalances in the relationship with state governments. This research employed a mixed-methods approach, including descriptive analysis, multicollinearity tests, factor analysis, and regression analysis, to assess the dynamics of state-local interactions. Primary data were gathered through interviews with local government officials, policymakers, and development experts, alongside questionnaires distributed within selected local governments. Secondary sources comprised government reports, academic literature, and policy documents. Three local governments were purposively selected from the state, with 400 questionnaires administered across Abeokuta North, Yewa North, and Sagamu local government. Findings indicate that local governments lack financial autonomy, with state approval required for service delivery and infrastructure projects, thereby hampering sustainable progress. Although a generally cooperative relationship exists, the financial dependence of local governments on state allocations due to the joint account system limits their accountability and capacity for independent infrastructure development. The study recommends enhancing local government autonomy through policy reforms, technical support, and staff training, alongside formalized communication protocols to strengthen intergovernmental collaboration. Keywords: State-local government relations, local government autonomy, poverty reduction, sustainable development, Nigeria